Managing major obstetric haemorrhage: Pharmacotherapy and transfusion. Issue 1 (March 2017) - Collis, Rachel; Guasch, Emilia
Abstract : Major obstetric haemorrhage is a leading cause of maternal mortality. A prescriptive approach to early recognition and management is critical to improving outcomes. Uterine atony is the primary cause of post-partum haemorrhage. First-line prevention and treatment include the administration of uterine tonic agents; other conservative measures include uterine cavity tamponade and uterine compression sutures. Interventional radiology procedures have been used for both prophylaxis and treatment, but a hysterectomy may be necessary if conservative measures fail. Assessment of anaemia and coagulation status is an important aspect of the management of haemorrhage. Hypofibrinogenaemia is a predictor of severe haemorrhage. Early and empiric use of fixed transfusion red blood cell:plasma:platelet ratios is controversial and may not be justified for all causes of haemorrhage. Cell salvage may be used safely in obstetric haemorrhage. Goal-directed therapy using point-of-care testing (e.g. thromboelastography) has not been well studied but holds promise for individualising resuscitation measures.